RISKS AND BENEFITS OF MINIMALLY INVASIVE SURGERY FOR DEGENERATIVE SPINE DISEASES - KARLLOS ADRYANO PRISCINOTTE RODRIGUES LIMA; PEDRO PEREIRA BARBOSA; MURYLLO HENRIQUE FERREIRA DE BRITO; MARCELA SOUZA CARVALHO DA COSTA PRISCINOTTE; JOÃO HENRIQUE MENESES XAVIER; WANDER JÚNIOR RIBEIRO (Coluna/Columna, 2025)
ABSTRACT Degenerative spinal diseases are anatomical conditions characterized by the deterioration of spinal structures, often associated with aging but also influenced by environmental and genetic factors. This study aimed to evaluate the risks and benefits of minimally invasive surgery (MIS) compared to traditional open surgery (OS) for degenerative spinal diseases, such as spinal stenosis and spondylolisthesis. A systematic literature review was conducted with a quantitative and qualitative approach to the collected data, structured according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), using the PubMed, Scopus, Web of Science, Medline, and Scielo databases. The total sample of the studies consisted of 900 patients with degenerative spinal diseases, with a mean age of 59 years ± 2.05. MIS presented several benefits compared to OS, including a significant reduction in intraoperative blood loss, shorter recovery time, lower levels of postoperative pain, fewer postoperative complications, and comparable functional outcomes, with reduced hospitalization time. In summary, MIS offers additional advantages, such as shorter hospital stays, less pain, and reduced complications, providing faster recovery and better quality of life for patients. Level of Evidence II; Systematic Review.